Simulation of neural behavior - Kitajima, Tatsuo; Feng, Zonggang; Azhim, Azran (InTech, 2016)
The brain is an organ that takes the central role in advanced information processing. There exist great many neurons in our brain, which build complicated neural networks. All information processing in the brain is accomplished by neural activity in the form of neural oscillations. In order to understand the mechanisms of information processing, it is necessary to clarify functions of neurons and neural networks. Although the current progress of experiment technology is remarkable, only experiments by themselves cannot uncover the behavior of only a single neuron. Computational neuroscience is a research field, which fills up the deficiency in experiments. By modeling the essential features of a neuron or a neural network, we can analyze their fundamental properties by computer simulation. In this chapter, one aspect of computational neuroscience is described. At the first, the cell membrane and a neuron can be modeled by using an RC circuit. Next, the Hodgkin-Huxley model is introduced, which has the function of generation of action potentials. Furthermore, many neurons show the subthreshold resonance phenomena, and the cell membrane is necessary to be modeled by an RLC circuit. Finally, some simulation results are shown, and properties of such neuronal behaviors are discussed.